Bank Soundness Level Analysis With The RGEC Approach - Rahman, Abdul; Muslim, Muslim (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aimed to determine the soundness level of banks using the rgec approach at Bank Agro, Bank Bukopin, and Bank BTN in the period 2016 -2018. This research evaluates four RGEC factors including Risk Profile factors through NPL and LDR ratios, Good Corporate Governance factors, Earning factors through ROA and NIM ratios, and Capital factors through CAR ratios. The population in this study are conventional banks listed on the Indonesia Stock Exchange from 2016 to 2018. Sampling was carried out in this study using purposive sampling. Based on the criteria set, the number of samples obtained is 3 companies. The data source used in this study is secondary data obtained from the company's annual financial reports published by each bank through the website of each bank. The data obtained in this study were analyzed descriptively. The results of this study indicate that the 3 banks, namely Bank Agro, Bank Bukopin and Bank BTN in the period 2013 to 2015 were overall healthy according to the RGEC approach. Keyword: